Trichobezoar Causing Airway Compromise during Esophagogastroduodenoscopy. (17th September 2015) - Kao, Erica Y.; Scalzitti, Nicholas J.; Dion, Gregory R.; Bowe, Sarah N.
Abstract : Objectives . (1) Report the case of a 5-year-old female with trichotillomania and trichophagia that suffered airway compromise during esophagogastroduodenoscopy for removal of a trichobezoar. (2) Provide management recommendations for an unusual foreign body causing extubation and partial airway obstruction. Methods . Case report of a rare situation of airway compromise caused by a trichobezoar. Results . A 5-year-old patient underwent endoscopic retrieval of a gastric trichobezoar (hairball) by the gastroenterology service under general endotracheal anesthesia in a sedation unit. During removal, the hairball, due to its large size, dislodged the endotracheal tube, effectively extubating the patient. The bezoar became lodged at the cricopharyngeus muscle. Attempts to remove the bezoar or reintubation were unsuccessful. The child was able to be mask ventilated while the otolaryngology service was called. Direct laryngoscopy revealed a hairball partially obstructing the view of the glottis from its position in the postcricoid area. The hairball, still entrapped in the snare from the esophagoscope, was grasped with Magill forceps and slowly extracted. The patient was then reintubated and the airway and esophagus were reevaluated. Conclusions . Trichobezoar is an uncommon cause of airway foreign body. Careful attention to airway management during these and similar foreign body extractions can prevent inadvertent extubations.